Spiritual Care at the Intersection of Mental Health: VA Chaplains’ Lived Experiences Supporting US Veterans - Martin Shaw; Kelsey B. White; Qiping Fan; Sarah F. Griffin; Amanda N. Stover (Journal of Religion and Health, 2026)
Abstract Chaplains play a vital role within the Department of Veterans Affairs (VA) by providing spiritual care and supporting veterans’ mental health needs. The present study explored 11 VA chaplains’ lived experiences regarding their support of veterans’ mental health. Using a phenomenological qualitative approach, it explored their motivations, perceptions of mental health patterns, collaborative practices, and assessments of training adequacy. Semi-structured interviews were conducted with a purposive sample of 11 VA chaplains. Interviews were transcribed and analyzed using thematic coding to identify themes reflecting chaplains’ lived experiences. Five primary themes emerged: (1) values and purpose underpinning veteran care; (2) veteran mental health patterns; (3) chaplain interventions; (4) collaboration with mental health professionals; and (5) education and training. The study supports the chaplains’ unique role at the intersection of spiritual and mental health care within the VA. While chaplains demonstrate increased awareness of veterans’ psychological and spiritual needs, gaps persist in the application of interventions. Strengthening collaborative practices and integrating mental health education within formal chaplain curricula and clinical training may enhance chaplains’ capacity to address mental health issues among veterans and foster supportive relationships with mental health professionals. Future research would benefit from mixed-methods approaches that could capture more comprehensive insights into the implementation of mental health initiatives.